Molecular mapping of resistance to bacterial stalk rot (Pectobacterium chrysanthemi pv. zeae Burk., McFad. and Dim.) in tropical white maize (Zea mays L.) - Canama, Alma O. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
We present the results of the first molecular mapping work on resistance to bacterial stalk rot (BSR) caused by Pectobacterium chrysanthemi pv. zeae Burk., McFad. and Dim. in tropical white maize. Molecular marker analysis of the P8 (BSR-susceptible) and YIF62 (BSR-resistant) parental inbred lines generated a total of 102 polymorphic simple sequence repeat (SSR), amplified fragment length polymorphism (AFLP) and resistance gene analog (RGA) polymerase chain reaction (PCR)-based DNA markers. Using the F 2 population of P8 × YIF62, we constructed a genetic linkage map consisting of 77 (35 SSR, 34 AFLP, 8 RGA) markers covering a distance of 932.8 cM with approximately 12.1 cM marker density, which is about 54% of the total map length of the maize standard map. Using the F 2 linkage map and phenotyping data from F 2:3 progenies, we identified a major genomic region located in chromosome 2 which was associated with resistance to BSR. The genomic region showed additive genetic effects which accounted for approximately 26% of the variation observed in BSR resistance.